Economic Analysis of the Situation of Tourist Arrivals in the Establishments of Tourists’ Reception with Functions of Tourist Accommodation in Romanian Rural - Duma, Daniela Aurelia; Blaga, Radu (Studia Universitatis Vasile Goldiș Arad, Seria Științe Economice, 2014)
Romanian tourism meet an upward trend in recent years due to more coherent strategies of the ministry, and the growth occurred in the service sector, which in recent years has outpaced other sectors of economic activity. Therefore we considered it necessary to analyze, the evolution of tourist arrivals in tourist accommodation, the situation overnight stays in tourist accommodation structures, analysis of the structures of reception with functions of tourist accommodation and situation of tourist accommodation capacity and activity in the areas. We used comparative methods to analyze statistical data taken from the Statistical Yearbook of Romania, the study stretching over a period of several years, and last but not least, analysis of land.